Red cell distribution width and its polygenic score in relation to mortality and cardiometabolic outcomes - Pan, Jingxue; Sun, Jiangming; Goncalves, Isabel; Kessler, Michael; Hao, Yan; Engström, Gunnar (Frontiers in Cardiovascular Medicine, 2023)
Abstract Introduction: Elevated red cell distribution width (RDW) has been associated with a range of health outcomes. This study aims to examine prognostic and etiological roles of RDW levels, both phenotypic and genetic predisposition, in predicting cardiovascular outcomes, diabetes, chronic kidney disease (CKD) and mortality. Methods: We studied 27141 middle-aged adults from the Malmö Diet and Cancer study (MDCS) with a mean follow up of 21 years. RDW was measured with a hematology analyzer on whole blood samples. Polygenic scores for RDW (PGS-RDW) were constructed for each participant using genetic data in MDCS and published summary statistics from genome-wide association study of RDW (n=408112). Cox proportional hazards regression was used to assess associations between RDW, PGS-RDW and cardiovascular outcomes, diabetes, CKD and mortality, respectively. Results: PGS-RDW was significantly associated with RDW (Pearson’s correlation coefficient=0.133, p<0.001). RDW was significantly associated with incidence of stroke (hazard ratio (HR) per 1 standard deviation=1.06, 95% confidence interval (CI): 1.02-1.10, p=0.003), atrial fibrillation (HR=1.09, 95%CI: 1.06-1.12, p<0.001), heart failure (HR=1.13, 95%CI: 1.08-1.19, p<0.001), venous thromboembolism (HR=1.21, 95%CI: 1.15-1.28, p<0.001), diabetes (HR=0.87, 95%CI: 0.84-0.90, p<0.001), CKD (HR=1.08, 95%CI: 1.03-1.13, p=0.004) and all-cause mortality (HR=1.18, 95%CI: 1.16-1.20, p<0.001). However, PGS-RDW was significantly associated with incidence of diabetes (HR=0.96, 95%CI:0.94-0.99, p=0.01), but not with any other tested outcomes. Discussion: RDW is associated with mortality and incidence of cardiovascular diseases, but a significant association between genetically determined RDW and incident cardiovascular diseases were not observed. However, both RDW and PGS-RDW were inversely associated with incidence of diabetes, suggesting a putative causal relationship. The relationship with incidence of diabetes needs to be further studied.